If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 4x + -5y + 7 Reorder the terms: 0 = 7 + 4x + -5y Solving 0 = 7 + 4x + -5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 0 + -4x = 7 + 4x + -4x + -5y Remove the zero: -4x = 7 + 4x + -4x + -5y Combine like terms: 4x + -4x = 0 -4x = 7 + 0 + -5y -4x = 7 + -5y Divide each side by '-4'. x = -1.75 + 1.25y Simplifying x = -1.75 + 1.25y
| 10+4x=16+x | | 9x-15=x+1 | | .18-.04x=.3+.04x | | -8(2t+8)=-32 | | K=3300+750x | | 2(f-1)=6 | | -10(s+2)=22 | | 10-(x+8)= | | 10+(x-8)= | | 4(t+1)=-4 | | 7(2t+4)=49 | | 21/y-8=3 | | 4(3s+3)=168 | | 4x^2-19x+39=6x+3 | | 2(2l+7)=58 | | 3(a-10)=24 | | (u-3)*7=28 | | 6y-5=-25 | | (q-9)*3=12 | | (e+4)*4=36 | | (x+2)(x-3)=20 | | (e+2)*5=35 | | 10-(x-8)= | | 14x+4y=55 | | 2x-(5+7x)= | | x^2-6x-26=-3x+2 | | 24-5x=12-7x | | 2x+(5+7x)= | | 6x+9=-46-5x | | 11x^2+22x-1200=0 | | 9+4x=12+x | | -19x-14=-10x+49 |